2020
DOI: 10.1111/jav.02320
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific variation in deterioration and degradability of avian feathers: the evolutionary role of microorganisms

Abstract: Feathers are essential for avian life, and factors affecting their integrity are important to understand their evolution. These factors should depend on, among other traits, species‐specific bacterial environments and life‐history characteristics. However, interspecific variation in feather deterioration, feather susceptibility to degradation by keratinolytic bacteria (degradability), and bacterial environment, have rarely been quantified. Here, we did so by measuring deterioration and degradability of wing fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Plumage degradation is continuous and starts already in the nest, in part through the action of feather‐degrading bacteria (Azcárate‐García et al., 2020), which are more active and prevalent in warm and humid environments (Burtt & Ichida, 2004). Accordingly, we found that both temperature and, to a lesser extent, precipitation correlated positively with the likelihood of complete post‐juvenile moult (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Plumage degradation is continuous and starts already in the nest, in part through the action of feather‐degrading bacteria (Azcárate‐García et al., 2020), which are more active and prevalent in warm and humid environments (Burtt & Ichida, 2004). Accordingly, we found that both temperature and, to a lesser extent, precipitation correlated positively with the likelihood of complete post‐juvenile moult (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The size of the uropygial gland has been shown to correlate positively with secondary sexual traits (Moreno-Rueda 2010), plumage brightness (Møller and Mateos-González 2019) and colour intensity (Amat et al 2011). Moreover, ornamental feathers are more easily degraded by bacteria (Ruiz-Rodríguez et al 2015;Azcárate-García et al 2020), and individuals with larger uropygial glands were those better protecting their ornamental feathers from degradation, which could result in more attractive plumage (Ruiz-Rodríguez et al 2015). Hence, secretions from the uropygial gland can be an important factor promoting the acquisition of gain extrapair copulations since several of these are likely to be condition-dependent (Andersson 1994).…”
Section: Modelmentioning
confidence: 99%
“…Feathers are nonliving integumentary structures that cover most of a bird's body and fulfill important functions, such as thermoregulation (Wolf & Walsberg, 2000), flight (Hedenström, 2002), and social signaling (Chaine et al, 2013). Due to degradation by mechanical abrasion and microorganisms (Azcárate‐García et al, 2020), or the need to adjust plumage to seasonal changes (Beltran et al, 2018), feathers need to be replaced regularly through molting to maintain their functionality. Molt is costly because it requires energy and other resources to grow feathers (Lindström, Visser, et al, 1993; Moreno‐Rueda, 2010; Murphy & King, 1992; Sanz et al, 2004) and because plumage function (e.g., flight ability) may be impaired during the molting process (Swaddle & Witter, 1997).…”
Section: Introductionmentioning
confidence: 99%